2016
DOI: 10.1038/ejhg.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal testing in Huntington disease: after the test, choices recommence

Abstract: The objective of this study was (1) to determine the impact of prenatal diagnosis (PND) for Huntington disease (HD) on subsequent reproductive choices and family structure; and (2) to assess whether children born after PND were informed of their genetic status. Out of 354 presymptomatic carriers of HD gene mutation, aged 18-45 years, 61 couples requested 101 PNDs. Fifty-four women, 29 female carriers and 25 spouses of male carriers, accepted to be interviewed (0.6-16.3 years after the last PND, median 6.5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…The threatened maternity or paternity is one of the most distressing situations for these subjects. When they decide to have children, they have yet to make another decision: whether or not to perform prenatal testing (Bouchghoul et al, 2016), and this option may only be considered feasible if the person is willing to terminate the pregnancy in the case of the fetus is a carrier of the mutated gene. Although all of these options are considered and assessed step by step, the reality is that subjects at-risk admit they feel overwhelmed because they must take a significant number of important decisions in a short space of time (Bouchghoul et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The threatened maternity or paternity is one of the most distressing situations for these subjects. When they decide to have children, they have yet to make another decision: whether or not to perform prenatal testing (Bouchghoul et al, 2016), and this option may only be considered feasible if the person is willing to terminate the pregnancy in the case of the fetus is a carrier of the mutated gene. Although all of these options are considered and assessed step by step, the reality is that subjects at-risk admit they feel overwhelmed because they must take a significant number of important decisions in a short space of time (Bouchghoul et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…When they decide to have children, they have yet to make another decision: whether or not to perform prenatal testing (Bouchghoul et al, 2016), and this option may only be considered feasible if the person is willing to terminate the pregnancy in the case of the fetus is a carrier of the mutated gene. Although all of these options are considered and assessed step by step, the reality is that subjects at-risk admit they feel overwhelmed because they must take a significant number of important decisions in a short space of time (Bouchghoul et al, 2016). Ethical (Kromberg & Wessels, 2013), legal (Freckelton, 2010(Freckelton, , 2014, financial, logistical and material aspects become the centre of general decisions related to life organization as a whole, depending on what is expected to happen to the subjects at-risk (Kromberg & Wessels, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study in France found that reproductive decisions in HD are made afresh with each pregnancy, which reflects our findings. 24 A conflict-prone or troubled relationship might also be anticipated more often in these couples but, contrary to this, thirteen of the couples relationships were perceived to be close and supportive. Decruyenaere et al 12 also found agreement between spouses in decision-making for reproductive choice in HD, and Bouchghoul et al 24 found no significant impact of the outcome of PND for HD on couples relationship status over time.…”
Section: Offer In-depth Counselling To All Couplesmentioning
confidence: 82%
“…Part of preparing couples for PND is establishing a defined timeline of events, often including set dates for an ultrasound dating scan, the CVS procedure, and the delivery of results. It is also known that waiting for the results of PND is difficult and distressing, 24,29 and that support with the practical arrangements for a TOP following unfavourable results is very important. 23 A number of couples in this cohort experienced delays during the PND process, which were thought to have contributed to their decisions to continue their pregnancies.…”
Section: Prepare Couples For the Reality Of The Process Of Pnd And Tementioning
confidence: 99%
See 1 more Smart Citation